Pendidikan Islam dan Manajemen (Urgensi Manajemen Pendidikan Pada Lembaga Pendidikan Islam) - Muid, Abdul; Arifin, Bustanul (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Many people want to know what is the difference between Islamic education management and conventional education management. For example, the management of public education is generally similar overall. This shows that most management rules can be used by all managers, but there are also some aspects that require different handling. The main basis of management in each field is the same, but the challenges that must be overcome vary depending on the field in which the management is applied and develops. Variations in these variables produce cultural variations which in turn cause variations.